183k views
2 votes
Write an expression with (-1) as its base that will produce a positive product

1 Answer

4 votes

The expression with '-1' as its base that will produce a positive product is


(-1)^(2n) , where n is a natural number.

If we take n=1, we get
(-1)^(2n)=(-1)^(2 * 1)= 1 which is positive.

If we take n=2, we get
(-1)^(2n)=(-1)^(2 * 2)= 1 which is also positive.

Similarly if we take any natural number in this expression, it will give a positive product.

Hence,
(-1)^(2n) is the required expression.

User MrL
by
5.7k points